Allele frequency distribution of hypervariable vntr D17s5 locus in chinese community in Unimas - Ann, Jessie Sim Chiew Ling. (Universiti Malaysia Sarawak (UNIMAS), 2006)
The high polymorphism characteristic of variable number or tandem repeats (VNTRs) have spurred studies based on it to be carried out and its applications covers a wide range which varies from genetic identification to population gel\etics and forensic medicine. For this study. alldc frequencies at. the hypervariable VNTR D17S5 locus were determined from the Chinese r)pulation sample in UNIMAS via the polymerase chain reaction (PCR) method. 50 samples we re analyzed out of the 75 samples collected and this yielded sufficient results for :-;lalistical evaluations. The distributions of the D17S5 alleles for the Chinese popUlation in UN IMAS wen: the highest in allele number 2 and lowest in allele number 5.